Intermediate PHP best practice for modern PHP development - Mitchell, Lorna Jane.; Safari eBooks ([S.l.] : O'Reilly Media, 2014)
"Take a practical tour of modern PHP best practices and learn why the language is experiencing a renaissance. In this video course, web development consultant Lorna Jane Mitchell demonstrates new features and capabilities of PHP, including improved support for object-oriented programming and the Data Objects (PDO) extension, with detailed examples. This course is ideal whether you're relatively new to the language or looking to update your existing skills-and incredibly helpful if you're developing a Drupal, WordPress, or Joomla site. Download this video or stream it through our HD player, and get up to speed on the great features recently introduced in PHP 5.x."--Resource description page.
Title from resource description page (viewed Sept. 2, 2014).
Presenter, Lorna Jane Mitchell.
Keywords: PHP (Computer program language); Application software -- Development; Electronic books